CHANGES IN MICROMORPHOMETRIC PARAMETERS OF VOIDS ALONG THE PROFILE OF ZONAL SOILS IN EUROPEAN RUSSIA - E. B. Skvortsova; K. N. Abrosimov; K. A. Romanenko (Бюллетень Почвенного института им. В.В. Докучаева)
The soils are distinguished by the presence and the profile distribution pattern of such pedogenic parameters as the organic matter content, available pedofeatures, structural state of the soil mass, etc. They differ in the organization of the pore space throughout the soil profile as well. Under discussion are results of computer micromorphometric analysis of fine macropores d = 0.2-2.0 mm in thin sections of vertical orientation from samples taken in genetic horizons of podzolic, soddy podzolic, gray forest soils and chernozems at the territory of European Russia. The profile changes in voids were analyzed using the most informative morphometric parameters such as the total area of the studied voids in thin sections, the content of fissure-like voids and those of vertical and/or horizontal orientation. The soil types under study showed differences in profile distribution of the above parameters. By analogy with the profile of carbonates, salts, organic matter it is proposed to recognize diagnostic profiles of the pore space represented as a system of voids in genetic horizons of the soil profile. Empiric profiles of the pore space reveal a great diversity. The most complicated organization of the pore space is inherent to soddy podzolic soils, the most simple “smoothed” profiles are characteristic of typical chernozems. The expert qualitative typization showed that the eluvial-illuvial and accumulative-eluvial-illuvial types are dominant among the studied empiric profiles of the pore space (42 and 30% respectively), what is explained by prevailing texture-differentiated soils. On the other hand, it makes possible to use the profile of the pore space as a diagnostic parameter of soils and soil formation processes.